Current processing and packing technology for space foods: a review. Issue 21 (29th November 2020) - Jiang, Jiahui; Zhang, Min; Bhandari, Bhesh; Cao, Ping
Abstract: With the launch of aerospace business, the national space agency has been working actively to improve the living environment of astronauts in outer space. Since 1980s, space food has been greatly enriched, except the differences in form, most of the foods on earth can be enjoyed in space. In this article, the space foods are classified, in general divided into five parts that include natural form food, intermediate moisture food, thermostabilized food, rehydrating food and irradiated food. New type of space food processing technology is also reviewed, including freeze-drying, irradiation sterilization, high pressure processing, microwave assisted thermal sterilization, food 3 D printing and the packaging of space food products, mainly including the packaging materials already used by the present space food system, and the feasibility analysis of some emerging high barrier packaging materials in the research stage. Finally, the review highlights the prospects of future space food system, including the development of in-orbit food preparation technology and the research of life support system.